A new approach to quantify angles and time of changes-of-direction during soccer matches - Kai, T.; Hirai, S.; Anbe, Y.; Takai, Y. (PLOS ONE, 2021)
Soccer players frequently perform change-of-directions (CODs) at various speeds during matches. However, tracking systems have shown limitations to measure these efforts. Therefore, the aim of the present study was to propose a new approach to measure CODs using a local positioning system (LPS), and clarify position-related difference in profile of CODs by using the approach.